PALEOCLIMATIC CONTROLS ON STABLE OXYGEN AND CARBON ISOTOPES IN CALICHE OF THE ABO FORMATION (PERMIAN), SOUTH-CENTRAL NEW-MEXICO, USA - Mack, G. H.; Cole, D. R.; Giordano, T. H.; Schaal, W. C.; Barcelos, J. H. (Sepm-soc Sedimentary Geology, 1991)
The stable oxygen and carbon isotopic composition of caliche in fluvial and supratidal rocks of the Abo Formation (Permian), south-central New Mexico, is controlled by palecoclimate and depositional environment. Fluvial caliche consists of low-Mg calcite nodules and vertically oriented tubules that display stage II texture. Micrite matrix support, brecciation, ooids/pisoliths, aveolar-septal texture, and peloids are common in the fluvial caliche and, along with red color and slickensides in the host shale, indicate pedogenesis in a well-oxidized vadose zone. In contrast, periodic waterlogging of the supratidal paleosols, probably due to high water table, is indicated by drab colors, carbonaceous flecks, horizontal rhizoliths, and the paucity of vadose textures in the stage II caliche nodules.Stable oxygen isotopes are similar in the fluvial and supratidal caliches and range from 21.6 to 30.5 parts per thousand (SMOW). The data exhibit a crude bimodality and delta-O-18 enrichment with a decrease in age (higher in the section). Consideration of these data in the context of delta-temperature relations suggests that 1) surface waters responsible for caliche formation increased in delta-O-18 (from roughly -8 to + 1 parts per thousand) over the 18 m.y. time interval that separated the lowest stratigraphic nodule horizon from the highest, 2) the increasing delta-O-18 values also reflect a warming trend (approximately 15-degrees to nearly 30-degrees-C) in the mean monthly temperature over this same time period, with perhaps an associated increase in Permian ocean temperatures, and 3) the significant variation in delta-O-18 from oldest to youngest caliche was probably enhanced by the amount effect, such that as the temperature increased, the amount of precipitation decreased, resulting in high delta-O-18 values.Caliches in the Abo are enriched in heavy carbon (-7.2 to -1.5 part per thousand PDB) compared to that of soil carbonate derived exclusively from C3 plants (-12 part per thousand PDB), and the supratidal caliches contain somewhat heavier carbon compared to the fluvial caliche. The delta-C-13 values for both environments increase with a decrease in caliche age. These results indicate that as the temperature increased and rainfall decreased with time, the level of C3 plant productivity apparently declined, allowing a greater influx of atmospheric CO2 into the soil. This can only occur when soil respiration rates are quite low or at very shallow depths (less than 10 cm), or both. Atmospheric CO2 seems to have invaded the supratidal soils to a somewhat greater extent than the fluvial soils.